Creating Sustainable, Cost-Effective, and Equitable Waste-Management Programs in Maine Communities - Deprez, Luisa; Deprez, Ron (Maine Policy Review, 2016)
The authors present several perspectives on popular municipal solid waste (MSW) policies and programs that can help guide decision making to address the waste hierarchy as well as to extend thinking in regard to MSW.
Keywords: waste management; Maine; municipal solid waste